Papillary glioneural tumor presenting with multiple ischemic strokes: an aggressive presentation of a “benign” entity - Vargas-Moreno, Alejandro; Cruz-Ramírez, Viviana; Meek-Benigni, Eugenio; Feo-Lee, Oscar (International Surgery Journal, 2021)
Papillary glioneural tumors are infrequent neoplasms of the central nervous system, classically presenting with an indolent clinical course, rarely being related to an aggressive presentation, and not being associated with ischemic or another type of paraneoplastic phenomena. We describe the first case of this type of presentation with a literature review of the current knowledge of this entity. A 16-year-old female presented with a hemorrhagic intra-axial lesion, confirmed to be a papillary glioneural tumor in the histopathological analysis, being associated with multiple ischemic cerebral and posterior fossa strokes without another discernable cause than the presence of a paraneoplastic syndrome, not previously reported with this type of neoplasms. A literature review is presented detailing the current knowledge about this entity and emphasizing the need for greater knowledge about its natural history, immunobiology and treatment alternatives, opening a new window for the study of this pathology and establishing the need for a strict follow-up of patients who have this kind of tumors in order to learn more about their evolution. The papillary glioneural tumor, a rare entity having generally with a benign course, can have different presentations. Greater knowledge is needed to understand this behavior in order to optimize patient’s outcomes.